A new monoterpenoid indole alkaloid from Ochrosia elliptica. Issue 13 (3rd July 2017) - Chen, A-Hong; Liu, Qing-Long; Ma, Yan-Lei; Jiang, Zhi-Hua; Tang, Jin-Ying; Liu, Yan-Ping; Chen, Guang-Ying; Fu, Yan-Hui; Xu, Wei
Abstract: A new monoterpenoid indole alkaloid, 10-methoxyakuammidine (1 ), together with four known alkaloids (2–5 ), were isolated from the stems and leaves of Ochrosia elliptica . The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparisons with data reported in the literature. New compound1 was evaluated for its cytotoxicities against five human cancer cell lines: HL-60, SMMC-7721, A-549, MCF-7 and SW480 in vitro .1 exhibited inhibitory effects with IC50 values comparable to those of cisplatin. Abstract :